Alpha 2 macroglobulin state in acute pancreatitis. Raised values of alpha 2 macroglobulin-protease complexes in severe and mild attacks. Issue 4 (April 1991) - Banks, R E; Evans, S W; Alexander, D; Van Leuven, F; Whicher, J T; McMahon, M J
Abstract : Plasma values of C reactive protein, alpha 1 proteinase inhibitor, alpha 2 macroglobulin, and complexed alpha 2 macroglobulin have been determined in serial samples from 27 patients with acute pancreatitis. Complexed alpha 2 macroglobulin was measured by a novel enzyme linked immunosorbent assay with a monoclonal antibody specific for the complexed form. Patients with severe illness had lower concentrations of total alpha 2 macroglobulin and higher concentrations of complexed alpha 2 macroglobulin than those with mild illness, and in the majority of severe attacks the abnormal amounts of complexed alpha 2 macroglobulin were present throughout the eight days of the study. The proportion of total alpha 2 macroglobulin in the uncomplexed form, however, was generally greater than 90%, and in 26% of the mild cases completely normal concentrations of uncomplexed alpha 2 macroglobulin (greater than 99% of total) were found throughout the eight days of the study. This suggests that exhaustion of alpha 2 macroglobulin in plasma is unlikely to be a major factor in the pathogenesis of acute pancreatitis.